Dreaming and awareness during dexmedetomidine- and propofol-induced unresponsiveness - L. Radek; R.E. Kallionpää; M. Karvonen; A. Scheinin; A. Maksimow; J. Långsjö K. Kaisti; T. Vahlberg; A. Revonsuo; H. Scheinin; K. Valli (ELSEVIER SCI LTD, 2022)
Background: Experiences during anaesthetic-induced unresponsiveness have previously been investigated by interviews after recovery. To explore whether experiences occur during drug administration, we interviewed participants during target-controlled infusion (TCI) of dexmedetomidine or propofol and after recovery.
Methods: Healthy participants received dexmedetomidine (n = 23) or propofol (n = 24) in stepwise increments until loss of responsiveness (LOR1). During TCI we attempted to arouse them for interview (return of responsiveness, ROR1). After the interview, if unresponsiveness ensued with the same dose (LOR2), the procedure was repeated (ROR2). Finally, the concentration was increased 1.5-fold to achieve presumable loss of consciousness (LOC), infusion terminated, and the participants interviewed upon recovery (ROR3). An emotional sound stimulus was presented during LORs and LOC, and memory for stimuli was assessed with recognition task after recovery. Interview transcripts were content analysed.
Results: Of participants receiving dexmedetomidine, 18/23 were arousable from LOR1 and LOR2. Of participants receiving propofol, 10/24 were arousable from LOR1 and two of four were arousable from LOR2. Of 93 interviews performed, 84% included experiences from periods of unresponsiveness (dexmedetomidine 90%, propofol 74%). Internally generated experiences (dreaming) were present in 86% of reports from unresponsive periods, while externally generated experiences (awareness) were rare and linked to brief arousals. No within drug differences in the prevalence or content of experiences during infusion vs after recovery were observed, but participants receiving dexmedetomidine reported dreaming and awareness more often. Participants receiving dexmedetomidine recognised the emotional sounds better than participants receiving propofol (42% vs 15%), but none reported references to sounds spontaneously.
Conclusion: Anaesthetic-induced unresponsiveness does not induce unconsciousness or necessarily even disconnectedness.